Bio-banding in academy football: player's perceptions of a maturity matched tournament. (4th July 2019) - Bradley, Ben; Johnson, David; Hill, Megan; McGee, Darragh; Kana-ah, Adam; Sharpin, Callum; Sharp, Peter; Kelly, Adam; Cumming, Sean P.; Malina, Robert M.
Abstract: Background: Individual differences in biological maturation impact player selection and development in youth football. Aim: To evaluate players perceptions of competing in a football tournament where they were matched by maturity rather than chronological age. Subjects: Participants included male junior footballers from three professional academies ( n =  115). Methods: The study employed multiple methods of analysis, including one sample mean t -tests, equivalence tests, ANOVAs, and thematic analysis of qualitative data derived from open-ended questions. Results and conclusions: Player's perceived the bio-banding format as providing two main benefits. Early maturing players perceived greater physical and technical challenge, and in turn new opportunities and challenges. Late maturing players perceived less physical and technical challenge, yet greater opportunity to demonstrate technical and tactical abilities. The players reported that they enjoyed and understood the purpose of the bio-banded format, and perceived less risk for injury. Players in all three maturity groups reported more opportunity to engage in leadership behaviours, influence game-play, and express themselves on the ball in the bio-banded format. Bio-banding may facilitate development for both early and late maturing academy players by presenting new learning environments and challenges.